Indonesia’s Renewable Energy Outlook: What to Expect in The Future Renewable Energy of Indonesia. A Brief Review - Ian Kurniawan; Reisya Ichwani; Richa Fionasari; Aryansyah Batubara; Adri Huda (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: The government of the Republic of Indonesia has reported that Indonesia potentially have more than 400,000 Megawatts (MW) of renewable energy by 2021. However, there is no comprehensive study about the trend of development and priority movement in the renewable energy sector. The main reason for the absence of this study is the lack of significant information and reports on the prospects for renewable energy in Indonesia. The present study aims to provide a basic understanding of renewable energy sector growth in Indonesia. The study uses quantitative analysis with the secondary data obtained from the literature. The result showed that the hydropower plant contributed the highest energy production in Indonesia followed by bioenergy, solar energy, and wind energy. Furthermore, the production trends of hydropower plants and bioenergy were relatively stagnant over the last 11 years, and the highest significant improvement was found in the solar energy sector. However, the number of solar energy production was far away from the targeted goal in RUEN (National Energy Master Plan/Rencana Utama Energi Nasional) 2017. The high cost of the solar energy sector become the main reason for the unsuccessful development of solar energy in Indonesia. Furthermore, several administrations and regulations were found to the political reasons which delay the energy transition improvement. The Government of the Republic of Indonesia must be able to improve and form regulations in the form of tax reduction regulations and electricity export-import subsidies to spur the growth and development of renewable energy in Indonesia. Opening up space for renewable energy investment in the public sector is a real contribution to society and is a solution to accelerate the achievement of the energy transition in Indonesia.Abstrak: Pemerintah Republik Indonesia telah melaporkan bahwa Indonesia memiliki potensi lebih dari 400.000 Megawatts (MW) Energi Baru dan Terbarukan (EBT) di tahun 2021. Namun, penelitian terhadap pola pengembangan dan pergerakan pengembangan EBT masih belum banyak ditemukan. Alasan utama dari tidak ditemukan penelitian ataupun studi tentang potensi EBT di Indonesia adalah keterbatasan informasi dan laporan terhadap prospek EBT di Indonesia. Studi ini bertujuan untuk menyediakan pemahaman dasar dari perkembangan sektor EBT di Indonesia. Studi ini menggunakan analisis kuantitatif dengan menggunakan data sekunder yang diperoleh dari berbagai literatur. Hasil menunjukkan bahwa Pembangkit Listrik Tenaga (PLT) Air menjadi sektor yang paling banyak memproduksi EBT di Indonesia disusul oleh PLT Bioenergi, PLT Surya, dan PLT Bayu. Namun, pola produksi energi menunjukkan PLT Air dan PLT Bioenergi menunjukkan produktivitas yang relative tetap pada 11 tahun terakhir dimana peningkatan produktivitas terbesar berada pada PLT Surya. Namun, jumlah produktivitas PLT Surya masih tergolong kecil jika dibandingkan dengan jumlah produksi target yang dilaporkan pada Rancangan Utama Energi Nasional (RUEN) 2017. Biaya yang tinggi dari PLT Surya menjadi alasan utama dari ketidakberhasilan pengembangan PLT Surya di Indonesia. Selain itu, beberapa alasan administratif dan regulasi ditemukan menjadi alasan politis yang dapat memperlambat pengembangan transisi energi di Indonesia. Pemerintah Republik Indonesia harus mampu memperbaiki dan membentuk regulasi berupa adanya regulasi pengurangan pajak dan subsidi ekspor-impor listrik untuk memacu pertumbuhan dan perkembangan energi terbarukan di Indonesia. Membuka ruang untuk investasi energi terbarukan ke sektor public merupakan kontribusi nyata ke masyarakat merupakan solusi untuk mempercepat pencapaian transisi energi di Indonesia.